(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2024)
Abstract Rapid development of science and technology, especially in the field of the internet was instrumental in various aspects of social life. Including in terms of information needs. As for the purpose of this research is to help make it easier in terms of admission to public schools or private way based website using PHP and MySQL as a database. Meanwhile, the methods used in the development of the system itself uses the model of the waterfall, i.e. by doing observation directly towards the object of research on systems that are running at the moment. Design your own system using object-oriented methods and in the design process is described using UML (Unfield Modelling Language). The resulting system was later expected to address the problems that exist and can help make it easier for prospective students who wish to register or the school in carrying out the activities of the acceptance of new students at the HIGH SCHOOL of AL-HUDA ISLAMIC EDUCATION CENTRE METROPOLITAN (IECM).